2023
DOI: 10.3390/su15021219
|View full text |Cite
|
Sign up to set email alerts
|

How Leadership Influences Open Government Data (OGD)-Driven Innovation: The Mediating Role of Organizational Commitment

Abstract: Open government data (OGD) are considered a sustainable driver of firm innovation. Leadership is a crucial decision-maker for firms to employ OGD in innovation. The present study focuses on two of the most prominent leadership styles: transformational and transactional. Drawing on the Organizational Commitment Theory, we claim that affective and normative commitment are the two parallel mechanisms that explain how leadership promotes OGD-driven innovation in firms. Our results show that transformational leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Organizational commitment serves as a mediator for leadership. Duarte et al (2021), Hadian Nasab and Afshari (2019), Ribeiro et al (2018), andZhou et al (2023) position organizational commitment as a mediator in building employee performance. Ribeiro et al (2020) and Semedo et al (2018) demonstrated commitment as a mediating factor between authentic leadership and the required work behaviors to support organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational commitment serves as a mediator for leadership. Duarte et al (2021), Hadian Nasab and Afshari (2019), Ribeiro et al (2018), andZhou et al (2023) position organizational commitment as a mediator in building employee performance. Ribeiro et al (2020) and Semedo et al (2018) demonstrated commitment as a mediating factor between authentic leadership and the required work behaviors to support organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational commitment is an emotional bond between employees and their work, leading to their willingness to continue participating (Saleem et al, 2019a). Zhou et al (2023) defined it as a logical contract with the organization, while Rodríguez-Rad and Sánchez del Rio-Vázquez (2023) defined it as the degree of psychological attachment to organizational membership. The dimensions of organizational commitment include affective commitment, continuance commitment, and normative commitment (Ribeiro et al, 2018;Saleem et al, 2019;Razzaq et al, 2019).…”
Section: Introductionmentioning
confidence: 99%